Cooperation between tropomyosin and α-actinin inhibits fimbrin association with actin filament networks in fission yeast - Christensen, Jenna R (eLife, 2019)
We previously discovered that competition between fission yeast actin binding proteins (ABPs) for binding F-actin facilitates their sorting to different cellular networks. Specifically, competition between endocytic actin patch ABPs fimbrin Fim1 and cofilin Adf1 enhances their activities, and prevents tropomyosin Cdc8’s association with actin patches. However, these interactions do not explain how Fim1 is prevented from associating strongly with other F-actin networks such as the contractile ring. Here, we identified α-actinin Ain1, a contractile ring ABP, as another Fim1 competitor. Fim1 competes with Ain1 for association with F-actin, which is dependent upon their F-actin residence time. While Fim1 outcompetes both Ain1 and Cdc8 individually, Cdc8 enhances the F-actin bundling activity of Ain1, allowing Ain1 to generate F-actin bundles that Cdc8 can bind in the presence of Fim1. Therefore, the combination of contractile ring ABPs Ain1 and Cdc8 is capable of inhibiting Fim1’s association with F-actin networks.